Strategi Guru PAI dalam Mengatasi Perilaku Bullying Secara Fisik Pada Siswa di SD IT Abu Bakar Ash-Shiddiq Keruak: Islamic Religious Education Teachers' Strategies in Addressing Physical Bullying Behavior Among Students at SD IT Abu Bakar Ash-Shiddiq Keruak - Lalu. A. Hery Qusyairi; Nasrullah; Diniati Hafizah (Al-Gafari : Manajemen dan Pendidikan, 2025)
Essentially, every child needs an education, as it allows them to develop their interests and talents. One way to develop these talents and interests is through formal or informal institutions. This research aims to find out the forms of physical bullying behavior at SD IT Abu Bakar Ash-Shiddia Keruak, to find out PAI teachers' strategies for dealing with physical bullying behavior at SD IT Abu Bakar Ash-Shiddiq Keruak and to find out the obstacles and solutions in dealing with it. the problem of physical bullying among students. The methods used in data collection were the observation method, interview method and documentation method. Based on the data obtained, the following research results were found, namely forms of bullying carried out by children such as pushing a friend's body, kicking. hitting, etc. There are two strategies used by PAI teachers in dealing with physical bullying behavior, the first is by using a lecture strategy. namely providing direction and advice to students, second is using a punishment strategy, namely cleaning we and muraja'ah as well as other punishments which are carried out after negotiating with the school and the students' parents. In realizing this strategy PAI teachers encounter several obstacles starting from students who do not respond to advice from parents who do not understand children's behavior at school, teachers who set poor examples and there are no written rules from school regarding bullying. So the solution is to provide guidance to students continuously, inform parents about student activities well, teachers change behavior to be better and will discuss making rules against bullying with the school.